2007
DOI: 10.1042/bj20070309
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for insulin as an autocrine growth factor for malignant brain tumour cells

Abstract: AT/RTs (atypical teratoid/rhabdoid tumours) of the CNS (central nervous system) are childhood malignancies associated with poor survival rates due to resistance to conventional treatments such as chemotherapy. We characterized a panel of human AT/RT and MRT (malignant rhabdoid tumour) cell lines for expression of RTKs (receptor tyrosine kinases) and their involvement in tumour growth and survival. When compared with normal brain tissue, AT/RT cell lines overexpressed the IR (insulin receptor) and the IGFIR (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…The potential of NVP-ADW742 and NVP-AEW541 as single agents or in combination with chemotherapeutic drugs human was investigated in acute myeloid leukemia, Ewing’s sarcoma, medulloblastoma, neuroblastoma, and small cell lung cancer (Scotlandi et al, 2005; Warshamana-Greene et al, 2005; Guerreiro et al, 2006b; Tanno et al, 2006; Doepfner et al, 2007; Tazzari et al, 2007; Urbanska et al, 2007). In atypical teratoid/rhabdoid tumor cells of the central nervous system, NVP-AEW541 was shown to inhibit cell proliferation and survival by blocking IGF-1R and IR activation by autocrine loops involving IGFs and insulin (Arcaro et al, 2007). In colorectal cancer, studies with NVP-AEW541 suggested that a combination therapy targeting both EGFR and IGF-1R could be a promising approach (Kaulfuss et al, 2009).…”
Section: Small Molecule Inhibitors Of the Igf-1r Tyrosine Kinase Actimentioning
confidence: 99%
“…The potential of NVP-ADW742 and NVP-AEW541 as single agents or in combination with chemotherapeutic drugs human was investigated in acute myeloid leukemia, Ewing’s sarcoma, medulloblastoma, neuroblastoma, and small cell lung cancer (Scotlandi et al, 2005; Warshamana-Greene et al, 2005; Guerreiro et al, 2006b; Tanno et al, 2006; Doepfner et al, 2007; Tazzari et al, 2007; Urbanska et al, 2007). In atypical teratoid/rhabdoid tumor cells of the central nervous system, NVP-AEW541 was shown to inhibit cell proliferation and survival by blocking IGF-1R and IR activation by autocrine loops involving IGFs and insulin (Arcaro et al, 2007). In colorectal cancer, studies with NVP-AEW541 suggested that a combination therapy targeting both EGFR and IGF-1R could be a promising approach (Kaulfuss et al, 2009).…”
Section: Small Molecule Inhibitors Of the Igf-1r Tyrosine Kinase Actimentioning
confidence: 99%
“…Further genetic factors, such as IGF-1 microsatellites, may account for possible effects on melanoma risk or its aggressiveness. A strong association between melanoma severity (expressed as Breslow index) and the IGF-1(CA) 19 repeat frequency was previously found. 50 Concomitantly, serum IGF-1 concentrations were mainly reduced in indi- 19 melanoma.…”
Section: Melanoma and Cell Proliferation Effects By Igf-1mentioning
confidence: 99%
“…A strong association between melanoma severity (expressed as Breslow index) and the IGF-1(CA) 19 repeat frequency was previously found. 50 Concomitantly, serum IGF-1 concentrations were mainly reduced in indi- 19 melanoma. Therefore, these results may have been obtained at diagnosis when melanoma was already present, suggesting that these concentrations could be a consequence of the cancer and its inflammatory component (generally decreased levels) 50 rather than a predisposition marker of tumor development (increased levels).…”
Section: Melanoma and Cell Proliferation Effects By Igf-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression was analyzed by immunoblotting as previously described (11,20) using antibodies specific for PI3K p110g, LYK5 (STRAD N-13), LKB1, MPP2 (Santa Cruz Biotechnology), AMPKa, phospho-Akt (Ser473; Thr308), ATR, phospho-S6 (Ser 235/236 and Ser 240/ 244), phospho-4E-BP1 (Cell Signaling Technology), and b-Actin (Sigma). The blots were quantified by densitometry using the software TotalLab Quant (TotalLab Limited).…”
Section: Western Blottingmentioning
confidence: 99%